A turizmus és az Európai Unión belüli területfejlesztés kölcsönhatása Spanyolország egy régiójában - Horváth, Péter (Acta Scientiarum Socialium, 2015)
The interaction of tourism and regional development in one region of Spain Tourism is the most important factor of economy of the Spanish Autonomous Community of Castilla y León, contributing to the regional GDP by 10,3% and giving job for 70 thousand people. Rural tourism in Spain is the most developed in this region. It contributes to maintaining the population of the region characterized by small settlements and helps to counterbalance the seasonal fluctuation of employment. The good performance of tourism is partly due to the fact that the tourism marketing of the region connects religious tourism (Saint James pilgrimage) with rural and cultural tourisms and partly to the successful realization of the projects of European Union in this area.
Keywords: rural tourism; Saint James pilgrimage; regional GDP; think small marketing; regional development